2015
DOI: 10.1111/pde.12688
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Pediatric Dermatology Service on Emergency Department Utilization for Children with Dermatitis

Abstract: This study provides a salient example of achieving the triple aim of health care reform: improving health outcomes (decreased ED visits) improving the patient experience (transitioning care from the ED to the more appropriate ambulatory clinical setting), and decreasing the cost of care (decreased ED charges).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…These encounters, termed here touchpoints, include admissions, emergency department (ED),urgent care and primary care provider (PCP) visits, and telephone encounters. 8,9 Touchpoints represent costs that may be mitigated if a patient is able to be evaluated by a dermatologist sooner.…”
Section: Stephens Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…These encounters, termed here touchpoints, include admissions, emergency department (ED),urgent care and primary care provider (PCP) visits, and telephone encounters. 8,9 Touchpoints represent costs that may be mitigated if a patient is able to be evaluated by a dermatologist sooner.…”
Section: Stephens Et Almentioning
confidence: 99%
“…While they wait, we suspected that patients may have multiple health care encounters related to a dermatologic complaint before formal evaluation by a dermatologist. These encounters, termed here touchpoints, include admissions, emergency department (ED),urgent care and primary care provider (PCP) visits, and telephone encounters . Touchpoints represent costs that may be mitigated if a patient is able to be evaluated by a dermatologist sooner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the studies found within this review, the most commonly evaluated intervention types were topical calcineurin inhibitors (n = 14), [15][16][17][18][19][20][21][22][23][24][25][26][27][28] followed by infant formula feeds intended to prevent eczema from developing (n = 10). [29][30][31][32][33][34][35][36][37][38] Six studies evaluated a change of service delivery, including the use of web-based consultations, 39 delivering care by a nurse practitioner, [40][41][42] the development of a paediatric dermatology service (although what this entailed was not described) 43 and the use of interdisciplinary group sessions with an educational counterpart. 44 Mason et al also evaluated an educational support programme, which included the provision of an educational DVD and telephone support.…”
Section: Resultsmentioning
confidence: 99%
“…41 While Boguniewicz et al did perform a cost analysis, the study focused more so on the development of a framework for assessing outcomes, intended to inform future research. 17 Four studies completed retrospective cost analyses using administrative databases, 21,22,43,60 and one feasibility study identified potential cost drivers for a future trial. 50 Only one study explored the potential methodological challenges in costing eczema interventions and care.…”
Section: Cost Studiesmentioning
confidence: 99%